Oxidative stress specifically downregulates survivin to promote breast tumour formation - Pervin, S (Nature Publishing Group, 2013)
BACKGROUND: Breast cancer, a heterogeneous disease has been broadly classified into oestrogen receptor positive (ER+) or oestrogen receptor negative (ER−) tumour types. Each of these tumours is dependent on specific signalling pathways for their progression. While high levels of survivin, an anti-apoptotic protein, increases aggressive behaviour in ER− breast tumours, oxidative stress (OS) promotes the progression of ER+ breast tumours. Mechanisms and molecular targets by which OS promotes tumourigenesis remain poorly understood. RESULTS: DETA-NONOate, a nitric oxide (NO)-donor induces OS in breast cancer cell lines by early re-localisation and downregulation of cellular survivin. Using in vivo models of HMLE(HRAS) xenografts and E2-induced breast tumours in ACI rats, we demonstrate that high OS downregulates survivin during initiation of tumourigenesis. Overexpression of survivin in HMLE(HRAS) cells led to a significant delay in tumour initiation and tumour volume in nude mice. This inverse relationship between survivin and OS was also observed in ER+ human breast tumours. We also demonstrate an upregulation of NADPH oxidase-1 (NOX1) and its activating protein p67, which are novel markers of OS in E2-induced tumours in ACI rats and as well as in ER+ human breast tumours. CONCLUSION: Our data, therefore, suggest that downregulation of survivin could be an important early event by which OS initiates breast tumour formation.